INFLUENCE OF “TRYFUZOL” ON HEALING OF BOARS AFTER CASTRATION WOUNDS - Кулинич, С. М. (Scientific Progress & Innovations, 2013)
According to the dynamics of morphological studies, the findings of the effectiveness of blood internal orbital injections of 1.0% solution “Tryfuzol” in a dose of 5 ml per animal were presented. It was found that after a single injection of the drug in the postoperative period, on the seventh day the reduction of the number of white blood cells is recorded, that is combined with the growth of granulocytes in leucogram. Changes in red blood cells are characterized by the decrease of red blood cell by 9.4% and 12.1% of the index of the size distribution of red blood cells.